High genetic diversity, phenotypic plasticity, and invasive potential of a recently introduced calcareous sponge, fast spreading across the Atlanto-Mediterranean basin - Guardiola, M.; Frotscher, J.; Uriz, M.-J. (Marine Biology, 2016)
Sponges are considered poor invaders and no genetic studies on introduced sponges have been performed up to now. Paraleucilla magna is the first calcareous sponge introduced to the Mediterranean and Northeastern Atlantic. The study aimed at investigating the genetic makeup and connectivity of the introduced populations of P. magna and at exploring signs of local phenotypic adaptation, to gain insight on the species invasive potential. Ten populations along the species introduction range (Brazil, Açores, Madeira, and continental Europe) were genetically characterized by using nine microsatellite markers. Most populations were genetically structured as suggested by significant Dst and Fst values, significant differences among populations (AMOVA) and the presence of private alleles. The analyzed populations belonged to three genetically homogeneous groups (K) according to the Bayesian algorithm (structure software) and the UPGMA dendrogram. Genetic diversity within populations was higher than expected. Recurrent introductions of non-randomly selected individuals from the native sources may have contributed to the heterozygote deficit found in all populations by forming pedigree structures with mating among relatives. Moreover, the species biological cycle was monitored in a population established on native Mediterranean assemblages (41°40′27″N, 2°47′25″E) and compared with the species cycle in other habitats. Contrasting life spans, growth habits, and reproduction cycles, depending on the habitat conditions, were recorded. To summarize, high genetic diversity, phenotypic local adaptation, and high reproduction rates altogether allow predicting the fast proliferation of P. magna in newly colonized regions and point to its strong invasive potential.